A Meta-Analysis Study The Influence of Leadership and Organizational Culture on Quality in Institutions Education - Ardianti, Vika; Triwiyanto, Teguh (Journal of Education for Sustainability and Diversity, 2024)
This study aims to analyze the influence of leadership and organizational culture on quality in educational institutions. The research method used is meta-analysis using 15 relevant studies in the form of articles and theses published in reputable national journals. This research uses research at all levels of education, namely basic education, secondary education, higher education and non-formal education. The meta-analysis results show that the average correlation coefficient is 0.568 with a standard deviation of correlation of 0.514. This means that H1 of this study is accepted and H0 is rejected in other words that there is an influence on leadership and organizational culture on quality in educational institutions.